A generalized effective anisotropic poroelastic model for periodically layered media accounting for both Biot’s global and interlayer flows - Milani, Marco (2016)
We present a generalized effective poroelastic model for periodically layered media in the mesoscopic scale range, which accounts for both Biot’s global and interlayer wave-induced fluid flow, as well as for the anisotropy associated with the layering. Correspondingly, it correctly predicts the existence of the fast and slow P-waves as well as quasi and pure S-waves. The proposed analytical model is validated through comparisons of the P-wave and S-wave phase velocity dispersion and attenuation characteristics with those inferred from a one-dimensional numerical solution of Biot’s poroelastic equations of motion. We also compare our model with the classical mesoscopic model of White for a range of scenarios. The results demonstrate that accounting for both wave-induced fluid flow mechanisms is essential when Biot’s global flow prevails at frequencies that are comparable or smallerwith respect to those governing interlayer flow. This is likely to be the case in media of high permeability, such as, for example, unconsolidated sediments, clean sandstones, karstic carbonates, or fractured rocks. Conversely, when interlayer flow occurs at smaller frequencies with respect to Biot’s global flow, the predictions of this model are in agreement with White’s model, which is based on quasi-static poroelasticity.